Explore Westonci.ca, the top Q&A platform where your questions are answered by professionals and enthusiasts alike. Ask your questions and receive detailed answers from professionals with extensive experience in various fields. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.
Sagot :
Next time, use the carrot for exponent like this:
x^2+7x+6=0
The first term is a , the second is b and the last is C
Quadratic is ax^2+bx+c=0
The formula is -(b) +- squareroot(b^2 -4(a)(c)) all over two a
So youve got:
-7 +- square root (49-4(1)(6)) divided by 2(1)
Simplify
-7 +- squareroot(49-24) / 2
-7 +- square root (25) / 2
25 is a perfect square of five, so tou have
(-7 + 5)/2 And (-7-5)/2
You answers should be : -1 & -6
x^2+7x+6=0
The first term is a , the second is b and the last is C
Quadratic is ax^2+bx+c=0
The formula is -(b) +- squareroot(b^2 -4(a)(c)) all over two a
So youve got:
-7 +- square root (49-4(1)(6)) divided by 2(1)
Simplify
-7 +- squareroot(49-24) / 2
-7 +- square root (25) / 2
25 is a perfect square of five, so tou have
(-7 + 5)/2 And (-7-5)/2
You answers should be : -1 & -6
x² + 7x + 6 = 0
x = -(7) +/- √((7)² - 4(1)(6))
2(1)
x = -7 +/- √(49 - 24)
2
x = -7 +/- √(25)
2
x = -7 +/- 5
2
x = -7 + 5 x = -7 - 5
2 2
x = 2 x = -12
2 2
x = 1 x = -6
The solution is equal to {1, -6}.
x = -(7) +/- √((7)² - 4(1)(6))
2(1)
x = -7 +/- √(49 - 24)
2
x = -7 +/- √(25)
2
x = -7 +/- 5
2
x = -7 + 5 x = -7 - 5
2 2
x = 2 x = -12
2 2
x = 1 x = -6
The solution is equal to {1, -6}.
We appreciate your time. Please revisit us for more reliable answers to any questions you may have. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Get the answers you need at Westonci.ca. Stay informed with our latest expert advice.